Problems of Adherence by Ukraine to International Commitments in Resolution of Cases in Trials that Took Place in Temporarily Occupied Territories - Basysta, Iryna; Galagan, Volodymyr (Kyiv-Mohyla Law and Politics Journal, 2018)
The legal procedure employed in criminal law where an individual was convicted by the courts of a temporarily occupied area of Ukraine has faced a number of challenges. When the European Court of Human Rights (ECHR) finds that Ukraine has run afoul of its international commitments during a trial, the records of such criminal proceedings shall be considered by the Supreme Court’s Grand Chamber, which shall apply the legal procedure regulations for newly discovered or exceptional circumstances, as outlined in Article 34 of the 2012 Criminal Procedure Code of Ukraine. At the same time, such hearing would be hindered by absence of reliable procedural regulations for retention of records in a criminal case in the occupied territory, and therefore are likely not available for review by the Supreme Court. In this article, the authors attempt to present both the objective challenges and the possible methods and means to address them to the international scholarly community. These challenges stand in the way of the reform of the Ukrainian judicial system as a whole, and particularly affect Ukraine’s adherence to its international commitments as it resolves of cases tried in the temporarily occupied territories. Considering the above, the authors analyzed the legislation and draft laws of Ukraine, as well as a number of international legislative documents, and outlined their own evidence-supported academic opinion on how to resolve the problem as well as articulated their approach to the organizational and legislative aspects of Ukraine’s adherence to its international commitments as the country’s courts resolve such criminal cases.